2019
DOI: 10.1186/s13071-019-3459-y
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito (Diptera: Culicidae) larval ecology in natural habitats in the cold temperate Patagonia region of Argentina

Abstract: Background Knowledge of immature habitats is an important focus for investigations of mosquito community ecology, and may improve our understanding of how environmental variables increase risk of mosquito-borne diseases by influencing the distributions and abundances of species. In Patagonia region, where climatic and ecological factors could be only borderline suitable for mosquito development, relatively little is known about larval ecology. The present study focuses on associations of environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Nevertheless, it is an indicator of water quality and productivity in aquatic habitats. A few recent works have reported that there is a strong correlation between habitat types, 72 larval abundance, 11,73 and mosquito species 74 with the dissolved oxygen level.…”
Section: Physicochemical Characteristicsmentioning
confidence: 99%
“…Nevertheless, it is an indicator of water quality and productivity in aquatic habitats. A few recent works have reported that there is a strong correlation between habitat types, 72 larval abundance, 11,73 and mosquito species 74 with the dissolved oxygen level.…”
Section: Physicochemical Characteristicsmentioning
confidence: 99%
“…For example, in Patagonia, Grech et al. (2019) found that the probability of finding the world’s most austral species of mosquito ( Aedes albifasciatus ) was positively associated with high wind speeds. In contrast, Magnussen (2010) found a negative effect of wind speed on aerial dispersal of Brachycera (Diptera) and Hymenoptera in the arctic region of Svalbard.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies testing the wind speed and ignoring its direction found contrasting wind effects on the community assembly of flying dispersers. For example, in Patagonia, Grech et al (2019) found that the probability of finding the world's most austral species of mosquito (Aedes albifasciatus) was positively associated with high wind speeds.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that under laboratory conditions, PACl coagulation-occulation could promote oviposition preference of female Culex pipiens pallens to some extent (compared with ordinary chlorine-free tap water), and has a very high lethal effect on the newborn mosquito larvae after hatching. The best chance what coagulation-occulation could achieve the highest lethal effect, is a lentic environment to keep the alum ocs at the bottom as long as possible, and it is exactly the environment what mosquito larvae need [17,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%